COMPARISON OF LEGAL CONSUMER PROTECTION SYSTEMS IN E-COMMERCE TRANSACTIONS TO SUPPORT DIGITAL ECONOMIC GROWTH IN INDONESIA - Fajar Sugianto; Ellora Sukardi; Tomy Michael (Tạp chí Khoa học Đại học Đà Lạt)
The e-commerce industry in Indonesia is growing rapidly amidst the slowdown in the country's economy. Moreover, most of the e-commerce business players in Indonesia are small, micro, and medium scale (SME). Consumers in e-commerce transactions have a greater risk of loss than business actors or merchants. In other words, consumer rights in e-commerce transactions are very vulnerable, so that consumers in e-commerce transactions are in a very weak bargaining position. The importance of a country regulating legal protection for consumers is generally based on considerations of its actuality and urgency. Legal regulations for e-commerce transactions are designed to create the level of certainty needed in business transactions and to protect consumers in e-commerce transactions in order to support the growth of the digital economy in Indonesia. Current legal protection regulations for consumers in Indonesia have not been able to protect consumers in cross-border e-commerce transactions. In e-commerce transactions, there are no national borders. The consumer protection laws of each country, such as those of Indonesia, are not sufficiently helpful because e-commerce operates across borders. This type of research is normative legal research that uses statutory regulations.